Acute Effects of Cinnamon Spice on Post-prandial Glucose and Insulin in Normal Weight and Overweight/Obese Subjects: A Pilot Study - Wang, Jing; Wang, Sijia; Yang, Jieping; Henning, Susanne M.; Ezzat-Zadeh, Zahra; Woo, Shih-Lung; Qin, Tianyu; Pan, Yajing; Tseng, Chi-Hong; Heber, David; Li, Zhaoping (Frontiers in Nutrition, 2021)
Clinical studies and meta-analyses have supported the notion that consuming cinnamon spice long term can have beneficial effects in individuals with normal glucose homeostasis and varying degrees of glucose intolerance including type 2 diabetes. The objective of this study was to evaluate the acute effect of cinnamon on the postprandial responses to a typical American breakfast in normal and overweight/obese participants (ClinicalTrials.gov registration No. NCT-pending). The consumption of a single dose of 6 g of cinnamon added to oatmeal prepared with milk resulted in a significant reduction of one of our primary outcomes postprandial insulin response (niAUC0-180min) in overweight/obese participants compared to control consuming breakfast without cinnamon. We also performed exploratory analysis of secondary outcomes. In normal weight participants, we observed a decrease of postprandial glucagon response (niAUC0-180min and glucagon levels at 60-120 min) and C-peptide response (30min) comparing breakfast with to without cinnamon. Cinnamon consumption did not change postprandial glycemic response in normal weight participants, but increased 60 min postprandial glucose in overweight/obese participants compared to control. In summary, cinnamon consumption differentially affected postprandial hormonal responses in normal and overweight/obese participants.